Outcome of retroarticular drilling for osteochondritis dissecans of the talus in a pediatric population. Issue 5 (July 2022) - Tan, Xue Wei; Joukhadar, Nabih; Leduc, Stéphane; Aubin, Carl-Éric; Hupin, Mathilde; Nault, Marie-Lyne
Abstract: Background: Outcomes of bone marrow stimulation for osteochondritis dissecans (OCD) of the talus in pediatric patients is not optimal. The objective was to evaluate the retroarticular drilling technique for talar OCD. Methods: A retrospective case-series study of pediatric cases treated for talar OCD with retroarticular drilling was done. Clinical and radiological outcome scores were recorded as follows: the percentage of patients who had a successful treatment, the percentage for every category of the Berndt and Harty treatment result grading and the percentage for every radiographical outcome score were computed. Results: Nineteen patients (18 girls; mean age: 14.6 ± 2.1 years) were included. The mean follow-up was 14.8 (±11.7) months. 26.3% required revision surgery. The Berndt and Harty scores were: 57.9% good, 10.5% fair, 31.6% poor. Radiological outcomes were: 21% healed, 47.4% partially healed, 31.6% no healing. The radiological outcome score was better for younger patients (P = 0.01) and those with an open physis (P = 0.001). Conclusion: 26.3% of patients needed revision surgery after talar OCD retroarticular drilling and 21% were healed radiographically. Skeletal immaturity and a younger age were associated to a better radiological outcome.